Novel electrical characteristic measurement system of semiconductor films for estimating device characteristics - Kook Chul Moon; Hwarim Im; Gyohyeok Yun; Hyoungsik Kim; JungUn Na; Changhwan Kim; Yong-Sang Kim (Journal of Information Display)
We proposed a novel measurement method and system to measure the electrical characteristics of non-patterned semiconductor films to estimate the final device’s properties. The proposed method is based on measuring bottom-gate structure thin-film transistor (TFT) using the probe pins as source and drain electrodes. We carefully designed the array structure and material of the probe pin to effectively detect extremely low-level currents without patterned electrodes on the semiconductor film. The contact pressure was also carefully controlled through continuous monitoring using an implemented pressure sensor to ensure the reliability and reproducibility of the measured data. In addition, we developed a method of extracting device parameters, such as the threshold voltage and field-effect mobility, from the measured data, considering the geometric factor of the proposed method. Comparative analysis between the measurement results of the film sample using the proposed system and that of the final TFT sample exhibited similar results with slight deviations. Furthermore, the proposed system provided similar results under repetitive measurements. Consequently, the proposed method and system successfully demonstrated the estimation of the final TFT’s properties by measuring the electrical characteristics of the non-patterned semiconductor film with excellent reliability, highlighting the possibility of effectively reducing costs for development and fabrication.